Pattern and Magnitude of Ocular Trauma Sustained in Road Traffic Accidents (A Trauma Centre Study): Doi: 10.36351/pjo.v38i4.1441 - Farooq, Fizzah; Muhammad Muneer Quraishy; Mazhar ul Hasan; Mehvash Hussain; Faiza Mushtaq (Pakistan Journal of Ophthalmology, 2022)
Purpose: To find out the pattern and magnitude of ocular trauma in road traffic accidents (RTA). Study Design: Descriptive cross sectional study. Place and Duration of Study: Shaheed Mohtarma Benazir Bhutto Trauma Centre, from September 2021 to December 2021. Methodology: Patients meeting the inclusion criteria had history and detailed examination. Data included age, gender, duration of presentation, eye involved, vehicle and type of eye trauma. Frequencies and percentages were computed for all categorical variables and mean and standard deviation was calculated for age. Effect modifiers like age, gender and vehicle were addressed through stratification. Effect of reporting time of injury, age, gender and type of vehicle involved in the pattern of injury was addressed. Post stratification chi-square was applied. P-value less than or equal to 0.05 was considered as significant. Results: Out of 117 patients, 81.1% were males and 18.9% were females. Average age was 29.88 ± 13.9 years. Maximum number of patients was in the age range of 10 – 20 years (35%). Two wheelers were 65.8%. Sixty five percent reported within 24hours of accident. Closed globe trauma accounted for 78.6% and contusion was found in 51 patients (43.6%). Among all, 66.7% had 6/6 – 6/9 visual acuity. No significant association of age and gender was found with pattern of ocular trauma. Reporting time and type of wheeler had association with type of ocular trauma and pattern of ocular trauma (p values less than 0.05). Conclusion: Ocular trauma is more common in young males and patients who report early have better visual acuity.